Huntsman sets out restructuring plan for pigments and additives business. Issue 2 (February 2015) - Unknown
Abstract : Following its recent US$1.1 billion Rockwood acquisition [ ADPO, December 2014], Huntsman Corp has announced a comprehensive restructuring programme designed to improve the global competitiveness of its pigments and additives business. As part of the plan, the company will reduce its workforce by approximately 900 positions worldwide. Annual cost savings are expected to be in the region of $130 million and will be achieved by the middle of 2016, Huntsman says.